Alteration of a specific microRNA regulating neprilysin expression in Alzheimer's disease. (1st February 2022) - Lahiri, Debomoy K; Wang, Ruizhi; Maloney, Bryan; Chopra, Nipun; Beck, John S; Counts, Scott E.
Abstract: Background: Alzheimer's disease (AD) is characterized by accumulation of amyloid β (Aβ) plaques and aggregates of hyperphosphorylated tau protein. Genetic, epigenetic, and environmental factors play critical roles in AD etiology (Maloney & Lahiri‐ Lancet Neurol‐ 15:760‐774); however, underlying mechanisms of pathogenesis remain unclear. Both Aβ biogenesis pathways, involving APP and BACE1, and degradation pathways, involving membrane metallo‐endopeptidase (MME), aka neprilysin, play critical roles in Aβ accumulation leading to AD. We posit that AD results from dysregulation of key biochemical pathways, particularly those involving non‐coding microRNA (miRNA) (Chopra et al, Mol. Psychiatry ‐2020). We hypothesize that since MME is an important Aβ‐clearing enzyme, disruption of miRNA regulation of MME would contribute to AD. Method: Bioinformatics prediction revealed miRNA binding sites on the MME mRNA 3'‐untranslated region (3'‐UTR). Neuronally differentiated human neuroblastoma (SK‐N‐SH) cells were transfected with either siRNA against MME, candidate miRNA mimics, miRNA‐inhibitors or negative controls. Levels of MME mRNA and protein were measured by qRT‐PCR and western blotting, respectively. miR‐181d emerged as a functional candidate. We tested sequence specificity and miR‐181d activity with reporter gene‐ MME 3'‐UTR fusion constructs. Levels of miR‐181d were quantified in human brain tissue specimens from control, MCI, and AD subjects. Result: Several human‐specific miRNAs were predicted to target the MME 3'‐UTR, including miR‐9, miR‐181d and miR‐216. Notably, miR‐181d treatment produced a significant reduction of MME mRNA and protein levels in neuronal cultures. Functional assays demonstrated miR‐181d activity. MME is expressed in several human organs, the highest in kidney. Levels of miR‐181d significantly influenced probability of AD diagnosis in human brain samples from temporal lobe and cerebellum but not posterior cingulate cortex. Overall, as miR‐181d levels increased, likelihood of AD increased. This trend was particularly strong in female subjects vs. male subjects. Presence of the APOE ε4 allele also increased likelihood of AD diagnosis, independent of miR‐181d levels. Conclusion: In human neuronal cultures, miR‐181d can down‐regulate MME mRNA and protein, potentially through the MME 3'‐UTR. Also, miR‐181d is elevated in AD brains in multiple regions. Since MME is a key Aβ‐degrading enzyme, its dysregulation by (presumably excess) miR‐181d could contribute to AD pathogenesis. Supported by the NIA/NIH grant P01AG014449 to DKL and SEC.